Compensation as a Determinant of Teacher Performance: A Case Study in Public Education - Andi Rahma Nur Alam; Rasmi Agustina; Mutmainna Andi Sudirman (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Lamappapoleonro, 2026)
This study aims to examine the effect of compensation on teacher performance within a public junior high school context. Honorary teachers play a crucial role in sustaining instructional activities in public education institutions; however, compensation-related challenges may influence their motivation and professional commitment. This research employs a quantitative explanatory approach using a census sampling technique involving 16 honorary teachers. Data were collected through structured questionnaires measured on a Likert scale and analyzed using simple linear regression with the assistance of SPSS. The results indicate that compensation has a positive and statistically significant effect on teacher performance (β = 0.450; p < 0.05). The standardized coefficient (Beta = 0.317) reflects a moderate positive relationship, suggesting that compensation contributes meaningfully to performance improvement, although it is not the sole determinant. The findings confirm that fair and adequate compensation can enhance instructional effectiveness, professional responsibility, and work engagement among honorary teachers.This study contributes to the human resource management literature in public education by providing empirical evidence from a localized institutional context. The results highlight the importance of integrating compensation policies with broader human resource strategies to achieve sustainable improvements in teacher performance